Sites, survey, and ceramics: Settlement patterns of the first to ninth centuries CE in the Upper Mun River Valley, northeast Thailand. (26th September 2016) - Evans, Caitlin; Chang, Nigel; Shimizu, Naho
Abstract : Our understanding of the transition from the last centuries of prehistory to the Pre-Angkorian period in northeast Thailand has been limited by a lack of projects bridging both periods. This article examines settlement patterns of the first to the ninth centuries CE in the Upper Mun River Valley based on recent (2012–14) surveys. The findings highlight the gradual settlement trends in the region, with a focus on local modification rather than the sudden adoption of external ideas. Results reinforce the fourth to sixth centuries CE as a pivotal period, when large centres consolidated and cautiously expanded upriver, into previously uninhabited regions. A relatively modest, flexible, and resilient settlement strategy developed, attuned to wider supra-regional trends, but allowing for the demands of the local cultural and physical landscape.